Study on possibility to design a compact Ring Main Unit (RMU) 11kv / Mohd Syaiful Mazlan Ahmad Samhudi - Ahmad Samhudi, Mohd Syaiful Mazlan (2007)
This paper presents a study on possibility to design a compact Ring Main Unit (RMU). The concept emphasizes more on two-dimensional (2D) simulation, steady-state condition and the simulation done based on finite element method software. In order to study the stress inside the RMU when normal condition, Finite Element Method (FEMLAB) is use to modeling and solving problems. FEMLAB is a powerful, interactive environment for modeling and solving problem based on partial differential equations (PDEs). FEMLAB is one of the techniques to study about of electrical stress or electric field inside the RMU. The material used for the simulation are silicon rubber for fuse's cover and copper for fuse's conductor and also air as empty space between fuses. The specification of all these material is given in Table 4.1.